THE DEVELOPMENT OF THE COURSE MODULE OF MANUFACTURING ENGINEERING DRAWING FOR VOCATIONAL STUDENTS - Riyadi, Andrian; Wibowo, Heri (Department of Mechanical Engineering Education, 2023)
This research developed a learning modules that fit the curriculum and determine the level of eligibility to be applied in learning of Manufacturing Drawing Engineering. This research applied a Research & Development methode with the 4D model from Thiagaradjan, that are Define, Design, Develop, and Disseminate. The developed course module was validated by material and media experts which is presented using Likert scale. The results of the validation from the lecturers as material experts scored 3,33 in very feasible category, the validation from the lecturers as media experts scored 3,35 in very feasible category, the validation from the teachers as material experts scored 3,04 in feasible category, and the validation from teachers as media experts scored 3,35 in very feasible category. Products that have been developed and revised were tested on 30 students of XI class in Mechanical Engineering department of SMK Negeri 3 Yogyakarta by distributing evaluation questionnaires to find out the responses of students. The product got a score 3,58 from the students in very feasible category. The module received a very feasible evaluation from lecturers as a material and media experts, teachers as a media experts, and students. The module received a feasible evaluation from teachers as a material experts.